The impact of HIV and AIDS on household food security and food acquisition strategies in South Africa - Kaschula, Sarah A H (Rhodes University, Faculty of Science, Department of Environmental Science, 2009)
How should the impact of HIV and AIDS on rural livelihoods be factored into efforts to monitor and stabilise household food security? With both HIV and AIDS and food security at the top of the global development agenda, this is a question posed by many scholars, practitioners, donor agencies and government departments. However, while there is an excess of discourse outlining the theoretical bases for how HIV and AIDS can, and is, radically transforming household food acquisition; there is a lack of empirical evidence from the South African context that demonstrates if, and how, HIV and AIDS changes household-level strategies of food acquisition and intake. This thesis explores the association of household-level mortality, chronic illness and additional child-dependent fostering with household experience of food security and food acquisition strategies, in three rural villages in the Eastern Cape and KwaZulu-Natal Provinces of South Africa. Qualitative and quantitative methods of data-collection were applied to 307 households in the three sites. For twelve months, both HIV and AIDS-afflicted and non-afflicted households were repeatedly visited at 3-month intervals, in order to be assessed for levels of food security, dietary intake and method of food procurement (purchased, cultivated, wild or donated). Overall, HIV and AIDS-afflicted households showed a significantly higher experience of food insecurity, probably attributable to shortages in food quantity. Dietary composition and overall diversity, however, was not significantly different. Although households with chronic illness and recent mortality showed a heightened investment in cultivation sources, the success of these strategies were to a great extent mediated by household income, and the level of medical treatment received by those who were chronically ill. Chronic illness was also associated with more donations, but these required considerable investments in social capital networks. Finally, use of wild leafy vegetables was not associated with household HIV and AIDS status, despite the financial, nutritional and labour-saving properties of these foods. Overall, the study suggests that there was little evidence of long-term planning and strategy in household food security responses. There was no evidence for shifts to labour-saving crops or foods and, in some instances, child labour was being used to ameliorate prime-adult labour deficits. Moreover, given that the vast majority (89.2%) of food groups were sourced through purchase, it is questionable whether investing in diverse food acquisition strategies would be advisable. Unless supported by medical treatment and steady earned household income, policies to promote intensified household agricultural subsistence production in the wake of HIV and AIDS are unlikely to provide households with anything more than short-term safety-nets, rather than long-term, sustainable food security solutions.
Keywords: Food security -- South Africa; Food supply -- South Africa; AIDS (Disease) -- Social aspects -- South Africa; HIV infections -- Social aspects -- South Africa; Chronically ill -- Economic conditions -- South Africa; Chronically ill -- Social conditions -- South Africa; Food -- Social aspects -- South Africa; Food -- Economic aspects -- South Africa; Rural development -- South Africa